Gambling to preserve price (and fiscal) stability - Giancarlo Corsetti; Bartosz Maćkowiak (European Central Bank (ECB), 2023)
We study a model in which policy aims at aggregate price stability. A fiscal imbalance materializes that, if uncorrected, must cause inflation, but the imbalance may get corrected in the future with some probability. By maintaining price stability in the near term, monetary policy can buy time for a correction to take place. The policy gamble may succeed, preserving price and fiscal stability, or fail, leading to a delayed, possibly large jump in the price level. The resulting dynamics resemble the models of a currency crisis following Krugman (1979) and Obstfeld (1986). Like in Obstfeld's work, multiple equilibria arise naturally: whether or not price stability is preserved may depend on private agents' expectations. The model can be reinterpreted as a model of partial default on public debt, in which case it is reminiscent of Calvo (1988).
Keywords: E31; F31; F41; 330; multiple equilibria; self-fulfilling beliefs; fiscal theory of the price level; inflation expectations; currency crisis; sovereign default